Strategi Manajemen Pelayanan Rawat Jalan untuk Meningkatkan Efektivitas Pelayanan Rumah Sakit - Fatmawati; Desi Hiratna (Manajerial dan Bisnis Tanjungpinang, 2026)
Outpatient services are one of the main service units in hospitals and play a crucial role in determining service quality and patient satisfaction. The high number of outpatient visits often leads to various problems such as long waiting times, limited human resources, and suboptimal service systems. These conditions require hospitals to implement effective management strategies to improve the quality and effectiveness of healthcare services. This study aims to analyze outpatient service management strategies to improve the effectiveness of hospital services. This study used a qualitative method with a descriptive approach. The research location was Permata Hospital in Cirebon. The research informants consisted of the head of the outpatient unit, doctors, nurses, administrative staff, and outpatients selected using a purposive sampling technique. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that outpatient service management strategies are implemented through optimizing human resources, utilizing information technology, improving coordination between service units, and periodically evaluating service quality. The implementation of an electronic queuing system and digitizing services helps improve service efficiency and reduce patient waiting times. Challenges faced include the high number of patient visits, limited healthcare personnel, and technical barriers to the service information system. Efforts to improve service effectiveness are being implemented through strengthening the concept of patient-centered care, training healthcare personnel, and routine service evaluation. The conclusion of this study indicates that outpatient service management strategies play a crucial role in improving the effectiveness of hospital services. Implementing appropriate management strategies can improve service quality, patient satisfaction, and hospital competitiveness.